2003
DOI: 10.1101/gr.463003
|View full text |Cite
|
Sign up to set email alerts
|

Y Chromosome STR Haplotypes and the Genetic Structure of U.S. Populations of African, European, and Hispanic Ancestry

Abstract: To investigate geographic structure within U.S. ethnic populations, we analyzed 1705 haplotypes on the basis of 9 short tandem repeat (STR) loci on the Y-chromosome from 9–11 groups each of African-Americans, European-Americans, and Hispanics. There were no significant differences in the distribution of Y-STR haplotypes among African-American groups, whereas European-American and Hispanic groups did exhibit significant geographic heterogeneity. However, the significant heterogeneity resulted from one sample; r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
68
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 34 publications
14
68
0
Order By: Relevance
“…Thus, studies in which individuals from Europe, sub-Saharan Africa, and Southeast Asia are used (e.g., Jorde et al 1997) might be an adequate description of the major components of the U.S. population (e.g., see Kayser et al 2003). However, it would be incorrect to conclude that such studies necessarily generalize to subdivisions of the human gene pool on a worldwide scale.…”
Section: Clines Not "Races"mentioning
confidence: 99%
“…Thus, studies in which individuals from Europe, sub-Saharan Africa, and Southeast Asia are used (e.g., Jorde et al 1997) might be an adequate description of the major components of the U.S. population (e.g., see Kayser et al 2003). However, it would be incorrect to conclude that such studies necessarily generalize to subdivisions of the human gene pool on a worldwide scale.…”
Section: Clines Not "Races"mentioning
confidence: 99%
“…For most of the samples, Y-STR data for the loci DYS19 (synonym DYS394), DYS389I, DYS389II, DYS390, DYS391, DYS392 and DYS393 were already available from our previous studies, 17,26,27 and for the remaining samples Y-STRs were analysed as described in detail on the website of the Y chromosome Haplotype Reference Database (YHRD) for US Populations (http:// www.ystr.org/usa). 23 Y-STR nomenclature is according to Kayser et al 15 except that DYS389II is considered without variation at DYS389I.…”
Section: Methodsmentioning
confidence: 99%
“…DNA sequencing of various length alleles of both loci was performed on ABI Prismt 377 DNA Sequencer (Applied Biosystems) using Big Dye chemistry (Applied Biosystems, Foster City, CA, USA) according to the recommendations of the manufacturer. For DYS385a, five different length alleles were sequenced (11,12,13,16,17), and for DYS385b eight alleles were sequenced (11,12,(14)(15)(16)(17)(18)20 Nei,37 was calculated using the software package Arlequin. 38 …”
Section: European Journal Of Human Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study in the US found no evidence that geography had a significant impact on genetic variation within several different ethnic groups. 38 Geographic differences in cultural or environmental factors may therefore be of greater importance to the observed regional disparities in disease susceptibility.…”
Section: Discussionmentioning
confidence: 99%